If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2u + -2) + -12u = 0 Reorder the terms: 5(-2 + 2u) + -12u = 0 (-2 * 5 + 2u * 5) + -12u = 0 (-10 + 10u) + -12u = 0 Combine like terms: 10u + -12u = -2u -10 + -2u = 0 Solving -10 + -2u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -2u = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -2u = 0 + 10 -2u = 0 + 10 Combine like terms: 0 + 10 = 10 -2u = 10 Divide each side by '-2'. u = -5 Simplifying u = -5
| 5m+2n-2m+9n= | | 2x+12=3x-8 | | 9+3r=-17 | | -72+11y+2=4(5y-2)-8 | | -2(2-5x)=8x-2 | | 14qp-51q^2+p^2= | | -5x-3x+9x=4-x | | 1/2x=1/4-6 | | w/7=3=-1 | | 2(2-5x)=8x-2 | | 13=-10y+3y | | 4(x-3)(x+4)=0 | | 5y-y=-12+y | | 2.5=(x-54166)/10200 | | 4(5x-3)+9=-2 | | (6x+2)(7x^2-5x-4)= | | 2x-10=38 | | -9r+1=-80 | | 3x8/3 | | mx^2+(2m-1)x+(m-1)=0 | | 5=x/4=1 | | 16=-10b+3b | | x^3-5x=-3 | | -8x-8=9x+43 | | 8(y-1)+5(y-1)= | | 5x+9y=-42 | | 2(x+6)-4(-x+3)=3(2x+1)-3 | | 2b*b*3a= | | -3x+2y=-34 | | -8(-x)-4(x-2)=8 | | 3S+45=10 | | 4(y-3)+3=8(2y+5) |